Isolation of a highly virulent Metarhizium strain targeting the tea pest, Ectropis obliqua - Zhao, Jie; Chen, Yuxi; Keyhani, Nemat O.; Wang, Cong; Li, Yichen; Pu, Huili; Li, Jincheng; Liu, Sen; Lai, Pengyu; Zhu, Mengjia; He, Xueyou; Cai, Shouping; et al. (Frontiers in Microbiology, 2023)
Introduction Tea is one of the most widely consumed beverages around the world. Larvae of the moth, Ectropis obliqua Prout (Geometridae, Lepidoptera), are one of the most destructive insect pests of tea in China. E. obliqua is a polyphagus insect that is of increasing concern due to the development of populations resistant to certain chemical insecticides. Microbial biological control agents offer an environmentally friendly and effective means for insect control that can be compatible with “green” and organic farming practices. Methods To identify novel E. obliqua biological control agents, soil and inset cadaver samples were collected from tea growing regions in the Fujian province, China. Isolates were analyzed morphologically and via molecular characterization to identity them at the species level. Laboratory and greenhouse insect bioassays were used to determine the effectiveness of the isolates for E. obliqua control. Results Eleven isolates corresponding to ten different species of Metarhizium were identified according to morphological and molecular analyses from soil and/or insect cadavers found on tea plants and/or in the surrounding soil sampled from eight different regions within the Fujian province, China. Four species of Metarhizium including M. clavatum, M. indigoticum, M. pemphigi, and M. phasmatodeae were documented for the first time in China, and the other species were identified as M. anisopliae, M. brunneum, M. lepidiotae, M. majus, M. pinghaense, and M. robertsii. Insect bioassays of the eleven isolates of Metarhizium revealed significant variation in the efficacy of each isolate to infect and kill E. obliqua. Metarhizium pingshaense (MaFZ-13) showed the highest virulence reaching a host target mortality rate of 93% in laboratory bioassays. The median lethal concentration (LC50) and median lethal time (LT50) values of M. pingshaense MaFZ-13 were 9.6 × 104 conidia/mL and 4.8 days, respectively. Greenhouse experiments and a time-dose-mortality (TDM) models were used to further evaluate and confirm the fungal pathogenic potential of M. pingshaense MaFZ-13 against E. obliqua larvae. Discussion Isolation of indigenous microbial biological control agents targeting specific pests is an effective approach for collecting resources that can be exploited for pest control with lowered obstacles to approval and commercialization. Our data show the presence of four different previously unreported Metarhizium species in China. Bioassays of the eleven different Metarhizium strains isolated revealed that each could infect and kill E. obliqua to different degrees with the newly isolated M. pingshaense MaFZ-13 strain representing a particularly highly virulent isolate potentially applicable for the control of E. obliqua larvae.